Fatty acid and metabolomic profiling approaches differentiate heterotrophic and mixotrophic culture conditions in a microalgal food supplement 'Euglena'. Issue 1 (December 2016) - Zeng, Min; Hao, Wenlong; Zou, Yongdong; Shi, Mengliang; Jiang, Yongguang; Xiao, Peng; Lei, Anping; Hu, Zhangli; Zhang, Weiwen; Zhao, Liqing; Wang, Jiangxin
Abstract Background Microalgae have been recognized as a good food source of natural biologically active ingredients. Among them, the green microalgaEuglena is a very promising food and nutritional supplements, providing high value-added poly-unsaturated fatty acids, paramylon and proteins. Different culture conditions could affect the chemical composition and food quality of microalgal cells. However, little information is available for distinguishing the different cellular changes especially the active ingredients including poly-saturated fatty acids and other metabolites under different culture conditions, such as light and dark. Results In this study, together with fatty acid profiling, we applied a gas chromatography–mass spectrometry (GC-MS)-based metabolomics to differentiate hetrotrophic and mixotrophic culture conditions. Conclusions This study suggests metabolomics can shed light on understanding metabolomic changes under different culture conditions and provides a theoretical basis for industrial applications of microalgae, as food with better high-quality active ingredients.